Lifestyle and blood pressure control in the Family Health Strategy Program, Pernambuco, Brazil - Martins Barbosa da Silva Paes, Isabella; Fontbonne, Annick; Pereira da Silva de Carvalho Melo, Silvia; de Melo Rodrigues, Heloisa; Pessoa Cesse, Eduarda Ângela (O Mundo da Saúde, 2018)
Blood pressure (BP) control - below 140 mmHg for systolic BP and 90 mmHg for diastolic BP, according to the Brazilian Society of Hypertension - reduces the risk of complications of hypertension. However, this control remains unsatisfactory in many hypertensive patients. In order to assess the size of the problem and the associated factors, blood pressure control and its association with socioeconomic, demographic, lifestyle and professional orientation characteristics were analyzed in a random sample of 784 hypertensive patients followed by the Family Health Strategy (FHS) in the state of Pernambuco. The dependent variable was BP control; the independent variables were age, gender, education, monthly family income, occupation, physical activity, adhering to a weight-reduction diet, smoking, frequency of alcohol consumption, and having been asked and/or advised by a FHS professional about: physical activity, necessity of losing weight, smoking and alcohol consumption habits. Chi-square and Student’s t tests were used for statistical analyzes. BP was controlled in 43.1% of the hypertensive patients. Control was more observed in women (p <0.001), younger subjects (p = 0.003), with higher education (p <0.001) who had been asked and /or advised about physical activity (p = 0.017) or the necessity of losing weight (p = 0.045).There was no association between BP control and lifestyle characteristics. These results point to the need for investment in actions that qualify the performance of the FHS professionals for greater control of hypertension in patients.